Mongolia : Environment and Natural Resource Management Socio-Economic Survey - Caparros, Alejandro (World Bank, Washington, DC, 2017)
Mongolia has very significant natural resources and a large part of the population is dependent on them for their daily living. The impact of the state of the environment on the living standards of herders is obvious, but also Mongolians living in the capital Ulaanbaatar have learned that air pollution, especially in winter, and other environmental problems have a deep impact on their living standards. The Government of the Netherlands has established a Trust Fund at the World Bank to support environmental activities in Mongolia. Under this framework, the World Bank contracted the first Environment and Natural Resource Management Socio-economic Survey for Mongolia (ENRMSS) to the National Statistical Office and an international consultant, the aim of this survey is to investigate public views on environmental issues and to measure the impact of environmental problems on human welfare, measured in economic terms. The first part of section five is devoted to wildlife hunting, fishing and wild nuts and fruits gathering, while the second part of this section focuses on energy consumption. Both complete and complement the information on consumption estimated in the Socioeconomic Survey (SES). Section six presents perception and opinions of herders on issues such as the number of animals in Mongolia or the best way to manage animal movements. Finally, section seven shows results on perceptions and opinions of Mongolians regarding nature and the environment.